Interwire and Intrawire Magnetostatic Interactions in Fe‐Au Barcode Nanowires with Alternating Ferromagnetically Strong and Weak Segments. Issue 47 (3rd October 2022) - Samardak, Aleksei Yu.; Jeon, Yoo Sang; Samardak, Vadim Yu.; Kozlov, Alexey G.; Rogachev, Kirill A.; Ognev, Alexey V.; Jeong, Eunjin; Kim, Gyu Won; Ko, Min Jun; Samardak, Alexander S.; Kim, Young Keun
Abstract: Metallic barcode nanowires (BNWs) composed of repeating heterogeneous segments fabricated by template‐assisted electrodeposition can offer extended functionality in magnetic, electrical, mechanical, and biomedical applications. The authors consider such nanostructures as a 3D system of magnetically interacting elements with magnetic behavior strongly affected by complex magnetostatic interactions. This study discusses the influence of geometrical parameters of segments on the character of their interactions and the overall magnetic behavior of the array of BNWs having alternating magnetization, because the Fe and Au segments are made of Fe‐Au alloys with high and low magnetizations. By controlling the applied current densities and the elapsed time in the electrodeposition, the dimension of the Fe‐Au BNWs can be regulated. This study reveals that the influence of the length of magnetically weak Au segments on the interaction field between nanowires is different for samples with magnetically strong 100 and 200 nm long Fe segments using the first‐order reversal curve (FORC) diagram method. With the help of micromagnetic simulations, three types of magnetostatic interactions in the BNW arrays are discovered and analy. This study demonstrates that the dominating type of interaction depends on the geometric parameters of the Fe and Au segments and the interwire and intrawire distances. Abstract : This study investigates the magnetic properties of metallic barcode nanowires composed of repeating Fe and Au segments fabricated by template‐assisted electrodeposition. It is demonstrated that the dominating type of interaction depends on the geometric parameters of the Fe and Au segments and the interwire and intrawire distances.